2006
DOI: 10.1017/s1074070800022628
|View full text |Cite
|
Sign up to set email alerts
|

West Virginia Farm Direct Marketing: A County Level Analysis

Abstract: To understand the factors that influence farm direct marketing, a linear regression model is estimated to test the relationships between county-level direct market sales and socioeconomic, agricultural production, and location characteristics for West Virginia. The results show that higher median housing value, increased population density, a younger population, a greater number of direct market farms, more diversity of fruit and vegetable production and closer proximity to Washington, D.C., increase direct ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Data on direct-to-consumer sales drawn from the 2007 Census of Agriculture does allow us to address factors correlated with supply and demand for local food and its spatial location. We based our conceptual model on the Brown et al (2006) county-level model of direct sales for West Virginia and extended it to encompass all U.S. counties and commuting zones, while accounting for detected spatial autocorrelation.…”
Section: Direct and Intermediated Marketing Of Local Foods In The Unimentioning
confidence: 99%
See 2 more Smart Citations
“…Data on direct-to-consumer sales drawn from the 2007 Census of Agriculture does allow us to address factors correlated with supply and demand for local food and its spatial location. We based our conceptual model on the Brown et al (2006) county-level model of direct sales for West Virginia and extended it to encompass all U.S. counties and commuting zones, while accounting for detected spatial autocorrelation.…”
Section: Direct and Intermediated Marketing Of Local Foods In The Unimentioning
confidence: 99%
“…Most studies on the determinants of local foods use survey data (e.g., Morgan and Alipoe, 2001; Lyson and Guptill, 2004; Brown et al, 2007), and a few have used secondary data (Thilmany and Watson, 2004; Brown et al, 2006). We attempted to model local food sales using 2008 ARMS data, but the sample size was too small to generate a statistically significant regression, precluding testing of the hypotheses.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a plethora of literature on DMSs as it pertains to consumer desirability and the attributes of consumers who buy directly from producers, there are relatively few studies that focus on producer behavior regarding DMSs and how participation in DMSs affects farm business income. For example, Brown et al () identified demographic and economic factors that influence DMS sales in West Virginia counties and found that counties’ fruit and vegetable production have a positive impact on county‐level DMS sales. On the other hand, the authors found that share of retired, part‐time, or limited resource farmers living in the county generated a lower income from a farmers’ market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature (Brown et al, ; Govindasamy et al, ; Monson et al, ) provides evidence that farms specializing in fruits, nuts, and nursery production are more likely to engage in direct marketing strategies.…”
mentioning
confidence: 99%